Digital Challenge, Analogue Mind-set: Assessing Indonesia’s Electronic Criminal Evidence Framework - Anton Hendrik Samudra; Subhajit Basu; Cristina Saenz Perez (Journal of Indonesian Legal Studies, 2026)
This article examines the treatment of electronic evidence in Indonesian criminal proceedings under the EIT Act and the new KUHAP. It argues that the new KUHAP has not succeeded in establishing coherent legal architecture for electronic evidence. Instead, the framework remains fragmented, under-specified, and anchored in an inherited analogue evidentiary mind-set. This is unsatisfactory because it encourages formalistic reliance on printed outputs, leaves the collection, authentication, handling, preservation, and evaluation of electronic evidence inadequately governed, and generates uncertainty for investigators, prosecutors, and judges. The article identifies the principal doctrinal and institutional defects in the current framework and assesses their implications for truth-seeking, procedural fairness, and the reliability of criminal adjudication. It further evaluates the emerging reliance on open-source electronic evidence and argues that the central weakness of the Indonesian approach lies not merely in legislative incompleteness, but in the absence of a principled evidentiary governance model for digital proof. Its principal contribution is to show that ISO standards can supply that missing framework by structuring the governance, handling, and assessment of electronic evidence and by correcting the mistaken assumption that digital proof can be accommodated within essentially analogue evidentiary categories.